Use of double sequential external defibrillation for refractory ventricular fibrillation during out-of-hospital cardiac arrest. (November 2016) - Cortez, Eric; Krebs, William; Davis, James; Keseg, David P.; Panchal, Ashish R.
Abstract: Introduction: Survival from out of hospital cardiac arrest (OHCA) is highest in victims with shockable rhythms when early CPR and rapid defibrillation are provided. However, a subset of individuals present with ventricular fibrillation (VF) that does not respond to defibrillation (refractory VF). One intervention that may be a possible option in refractory VF is double sequential external defibrillation (DSD). The objective of this case series was to describe the outcome of prehospital victims with refractory VF treated with DSD in the out-of-hospital setting. Methods: This evaluation is a retrospective chart review of VF patients treated with DSD in the prehospital setting from August 1st, 2010 through June 30th, 2014. Patients were excluded if less than 17 years of age. The outcomes we evaluated were the number of patients with return of spontaneous circulation, conversion from VF, survival-to-hospital discharge, and Cerebral Performance Category score. Results: Total of 2428 OHCA events were reviewed with twelve patients treated with DSD. Median DSD and prehospital resuscitation times were 27 min (IQR 22–33) and 32 (IQR 24–38), respectively. Of the 12 patients treated, return of spontaneous circulation was achieved in three patients, nine patients were converted out of ventricular fibrillation, three patients survived to hospital discharge, and two patients (2/12, 17%) were discharged with Cerebral Performance Category scores of 1 (good cerebral performance). Conclusions: Double sequential defibrillation may be another tool to improve neurologically intact survival from OHCA. Further studies are needed to demonstrate direct benefits to patient outcomes.